Metodologia evaluării calităţii vieţii în mediul educaţional: rolul expertizei în elaborarea şi validarea instrumentelor de evaluare [Articol] - Platon, Carolina; Bolea, Zinaida; Turchină, Tatiana (CEP USM, 2012)
Articolul reflectă opinia autorilor cu privire la rolul expertizei în elaborarea şi validarea instrumentelor de evaluare. Sunt analizate criteriile de selectare a experţilor reflectate în literatura de specialitate. Sunt prezentate rezultatele abordării empirice privind definirea criteriilor de selecţie a experţilor pentru evaluarea calităţii vieţii în mediul educaţional în Republica Moldova.

The article reflects the author’s opinion about the role of the expertise in the elaboration and validation of the evaluation instruments. The criteria for the selection of experts that are reflected in the specialized literature have been analyzed. The results of an empiric approach regarding the identification of the criteria for selection of experts suitable for elaboration of the methodology of evaluation of the life quality in the educational environment of Moldova are presented.
THE METHODOLOGY OF EVALUATION OF LIFE QUALITY IN THE EDUCATIONAL ENVIRONMENT: THE ROLE OF THE EXPERTISE IN THE ELABORATION AND VALIDATION OF THE EVALUATION INSTRUMENTS
Keywords: expertiză; criteriu; selecţie